Delivery of VEGF and delta-like 4 to synergistically regenerate capillaries and arterioles in ischemic limbs. (15th April 2022) - Niu, Hong; Gao, Ning; Dang, Yu; Guan, Ya; Guan, Jianjun
Abstract: Vascularization of the poorly vascularized limbs affected by critical limb ischemia (CLI) is necessary to salvage the limbs and avoid amputation. Effective vascularization requires forming not only capillaries, but also arterioles and vessel branching. These processes rely on the survival, migration and morphogenesis of endothelial cells in the ischemic limbs. Yet endothelial cell functions are impaired by the upregulated TGFβ. Herein, we developed an injectable hydrogel-based drug release system capable of delivering both VEGF and Dll4 to synergistically restore endothelial cellular functions, leading to accelerated formation of capillaries, arterioles and vessel branching. In vitro, the Dll4 and VEGF synergistically promoted the human arterial endothelial cell (HAEC) survival, migration, and formation of filopodial structure, lumens, and branches under the elevated TGFβ1 condition mimicking that of the ischemic limbs. The synergistic effect was resulted from activating VEGFR2, Notch-1 and Erk1/2 signaling pathways. After delivering the Dll4 and VEGF via an injectable and thermosensitive hydrogel to the ischemic mouse hindlimbs, 95% of blood perfusion was restored at day 14, significantly higher than delivery of Dll4 or VEGF only. The released Dll4 and VEGF significantly increased density of capillaries and arterioles, vessel branching point density, and proliferating cell density. Besides, the delivery of Dll4 and VEGF stimulated skeletal muscle regeneration and improved muscle function. Overall, the developed hydrogel-based Dll4 and VEGF delivery system promoted ischemic limb vascularization and muscle regeneration. Statement of significance: Effective vascularization of the poorly vascularized limbs affected by critical limb ischemia (CLI) requires forming not only capillaries, but also arterioles and vessel branching. These processes rely on the survival, migration and morphogenesis of endothelial cells. Yet endothelial cell functions are impaired by the upregulated TGFβ in the ischemic limbs. Herein, we developed an injectable hydrogel-based drug release system capable of delivering both VEGF and Dll4 to synergistically restore endothelial cell functions, leading to accelerated formation of capillaries, arterioles and vessel branching. Graphical abstract: Image, graphical abstract